Ecological role of extrafloral nectar secretion and Acacia food body proteins and their relation with nitrogen fluxes in the Acacia-Pseudomyrmex mutualism - Orona Tamayo, Domancar (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
Mutualisms are interactions between different species that provide services and rewards with benefits in the adequacy of both parties. In the Acacia-Pseudomyrmex interaction, the plants provide rewards to their defender ants by providing them with nutritious granules (FBs) an exclusive food for the nutrition of ant larvae, extrafloral nectar (NEF) on which adult ants feed and a nesting place in spines. hollow for the entire colony. In return, the ant defends the host plant from herbivorous insects and competent plants. As in all mutualisms, the Acacia-ant interaction is prone to exploitation by organisms that are not reciprocal, exploiter ants like Pseudomyrmex gracilis, live and feed on the rewards produced by mutualistic acacias and do not give the payment that is the service of the protection. The objective of the present study was to understand how reward production is optimized in this mutualism. Thus, it was investigated: (i) how FBs are protected from consumption by exploiters, (ii) how NEF production is controlled and optimized and (iii) how mutualistic ants manage to supplement their nitrogen demand with a strictly based diet in rewards derived from the plant. Protein extraction and massive sequencing of these biomolecules were carried out in FBs from Acacia hindsii and Acacia cornigera plants, finding the presence of Kunitz-type protease inhibitors (PIs). The larvae of mutualistic ants use chymotrypsin and elastase type proteases as the main proteolytic enzymes (responsible for the digestion of FBs), however, the activities of these digestive enzymes in exploiter ants were lower.

Los mutualismos son interacciones entre diferentes especies que brindan servicios y recompensas con beneficios en la adecuación de ambas partes. En la interacción Acacia-Pseudomyrmex, las plantas proveen recompensas a sus hormigas defensoras brindándoles gránulos nutritivos (FBs) un alimento exclusivo para la nutrición de larvas de hormiga, néctar extrafloral (NEF) del cual se alimentan las hormigas adultas y lugar de anidamiento en espinas huecas para toda la colonia. A cambio la hormiga defiende a la planta hospedera de insectos herbívoros y plantas competentes. Como en todos los mutualismos, la interacción Acacia-hormiga es propensa a la explotación por organismos que no son recíprocos, hormigas explotadoras como Pseudomyrmex gracilis, viven y se alimentan de las recompensas producidas por acacias mutualistas y no dan el pago que es el servicio de la protección. El objetivo del presente estudio fue entender como la producción de recompensas es optimizada en este mutualismo. Es así que se investigó: (i) como los FBs son protegidos del consumo por explotadores, (ii) como la producción de NEF es controlada y optimizada y (iii) como las hormigas mutualistas logran suplementar su demanda de nitrógeno con una dieta estrictamente basada en recompensas derivadas de la planta. En FBs de plantas de Acacia hindsii y Acacia cornigera se llevó a cabo una extracción de proteínas y una secuenciación masiva de estas biomoléculas, encontrándose la presencia de inhibidores de proteasas tipo Kunitz (IPs). Las larvas de hormigas mutualistas utilizan proteasas tipo quimotripsina y elastasa como principales enzimas proteolíticas (responsables de la digestión de los FBs), sin embargo, las actividades de estas enzimas digestivas en hormigas explotadoras fueron menores.
Instituto de Investigaciones Agropecuarias y Forestales. Instituto de Investigaciones sobre los Recursos Naturales. Instituto de Investigaciones Químico Biológicas. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Químico Farmacobiología. Programa Institucional de Doctorado en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; IIQB-D-2013-1659; Opción en Biología Experimental; Proteínas; Acacia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3769